Assessment of inflow boundary conditions for RANS simulations of neutral ABL and wind turbine wake flow. Issue 179 (August 2018) - Tian, Linlin; Zhao, Ning; Wang, Tongguang; Zhu, Weijun; Shen, Wenzhong
Abstract: It is known that wind turbines actually operate in the lower part of the atmospheric boundary layer (ABL), the modelling of this ABL flow is an important precondition for the simulations of wind turbine wakes. So, the capabilities of various inlet boundary conditions with related modelling methodologies in constructing equilibrium ABL are assessed firstly through cases of ABL flows over uniformly rough terrain, to ascertain that there are no substantial changes in the prescribed profiles throughout the whole computational domain. In this process, six popular turbulence inflow profiles, including four uniform and two non-uniform ones, are considered and investigated. Then, sensitivity studies on inflow profiles for predicting wind turbine wake development are carried out. Through comparing with the Sexbierum field experimental data, in terms of wake velocity and turbulence intensity along the cross-wind direction at several downstream positions, this study finds out that the shape and magnitude of wake velocity and wake turbulence profiles are significantly affected by different inflow profiles. Possible reasons for this sensibility are discussed, and accordingly, some suggestions are given to improve the accuracy of wind turbine wake simulation. Highlights: A neutral atmospheric boundary layer (ABL) flow over uniformly rough terrain is modelled. The capabilities of various inflow profiles and related modelling methodologies in constructing neutral ABL are assessed. Sensitivity studies on inflow profiles for predicting wind turbine wake development are carried out. The results reveal that wake performance is significantly affected by different commonly-used inflow profiles. Some suggestions are given to improve the accuracy of wind turbine wake simulation.